Los espacios de agua romanos y su influencia en el ocio acuático del siglo XIX - Zozaya-Montes, Maria (2013)
Here are analyzed the Iberian Spa and Healt Resorts (balnearios) of the XIXth Century, studying the revival of roman "Termae" culture in material and symbolic terms.